Telecommunications services in developing countries : tax, trade, and mobile money - (:unkn) unknown (My University, 2022)
Telecommunications is one of the most dynamic sectors in many developing countries. Telecommunication services improve both the productivity of economies and the well-being of individuals. There are significant advantages in promoting digital inclusion through broader mobile phone network coverage and affordable access and usage costs as well. However, since 2004, many countries have increased telecommunications’ tax burden through special taxes on mobile network operators (MNOs) or consumers. For MNOs, such policies may hurt innovation and investment in the sector and widen the digital divide between industrialized and developing countries. The purpose of this thesis is to explore several issues raised by the development of telecommunication services in developing countries by addressing the following questions: What is the tax burden on telecommunications companies? How does the demand for telecommunication services vary with prices? How could innovations in the telecommunications sector help governments promote the diffusion of positive externalities? Chapter 1 measures the tax burden on MNOs through the Average Effective Tax Rate (AETR) in twenty-five African countries. This tax burden encompasses general and special taxes under the Ministry of Finance's (MoF) control and fees raised by the national telecommunication Regulatory Agency (RA). For instance, the AETR varies significantly across countries, ranging from 33 percent in Ethiopia to 118 percent in Niger. Also, special taxes and fees represent a large share of the AETR, illustrating some taxation by regulation and a potential tax competition (a race to the top) between the MoF and the RA.Chapter 2 estimates the demand price elasticity of mobile voice communication in developed and developing countries using quarterly operator data from 2000 to 2017. It finds that for developed countries, the demand is more price elastic, and voice communication is a substitute for internet data usage. Anoth
Keywords: African Research